Judicialização da saúde, justiça e resolutividade: um perfil do usuário-litigante na Comarca de Matelândia/PR - Santos, Rodrigo Arthur dos (2017)
Judicialization is the transference of the power of the elected authorities to the judiciary, materialized in a proactive action by the judges, in the judicial review and in the realization of fundamental rights, such as, health, which must be materialized by the State. If the contemplation of this right is usually given by the judicial actions instead of the elected powers, the judicialization of health occurs. This is caused by the inertia of the majority powers, the advancement of democracy, etc. This phenomenon is subject to criticism regarding the separation of powers, disorganization of the administration, reserve of the possibilities and the definition of the concept of right to health. Before this framework, a profile of the user-litigant will be drawn and it will be analyzed if the judicialization is a way democratization of access to justice, citizenship and empowerment of the population or if it makes the benefit available for the elite in the District of Matelândia/PR. Therefore, it will be assessed if the judicialization is a phenomenon to be fought, tolerated or Stimulated.